The everyday lives of sovereignty political imagination beyond the state - Bryant, Rebecca; Reeves, Madeleine (Cornell University Press, 2021)
Around the world today, border walls and nationalisms are on the rise as people express desires to "take back" sovereignty. This collection uses ethnographic research in disputed and exceptional places to study sovereignty claims from the ground up. While it might immediately seem that citizens desire a stronger state, the cases of compromised, contested, or failed sovereignty in this volume point instead to political imaginations beyond the state form. Authors use cases from Spain to Afghanistan, Western Sahara to Taiwan, to show how calls to take back control or to bring back order are best understood as longings for sovereign agency. By paying close ethnographic attention to these desires and their consequences, The Everyday Lives of Sovereignty offers a new way to understand why these yearnings have such profound political resonance in a globally interconnected world
"A number of the papers published here were originally presented in October 2015 at the conference "The Everyday Lives of Sovereignty," held in Nicosia, Cyprus" - aus der Danksagung
Keywords: Anthropology; International Studies; Political Science & Political History; POLITICAL SCIENCE / Constitutions; Sovereignty; Souveränität; Politische Anthropologie; Staat; Aufsatzsammlung; Konferenzschrift -- 2015 -- Nikosia